Successful treatment of gastric cancer after complete response of lung cancer by nivolumab: a case report - Shunji Endo; Yoshinori Fujiwara; Koji Kurose; Masaharu Higashida; Hisako Kubota; Yuko Okamoto; Shumei Mineta; Hironori Tanaka; Toshimasa Okada; Atsushi Tsuruta; Takashi Akiyama; Toru Oga; et al. (Surgical Case Reports, 2020)
Abstract Background Nivolumab is effective for gastric cancer and lung cancer, but complete response is rare. We experienced a case of synchronous gastric cancer and lung cancer who was treated by nivolumab and laparoscopic gastrectomy. Case presentation A 63-year-old male consulted our institution and was found to have gastric cancer cT1(SM)N0M0 Stage IA and lung cancer cT2N2M1(PUL) Stage IV. He received eight chemotherapy treatments plus radiation, but the lung disease remained progressive. Finally, he received nivolumab therapy and complete response of both cancers was obtained. The gastric cancer recurred, but was successfully treated by laparoscopic gastrectomy. The resected specimen revealed three lesions, each being pT1aN0M0 Stage IA. The primary gastric cancer seemed to have completely vanished without scarring. Conclusions This was thought to be a rare case of gastric cancer recurrence after complete response of gastric cancer and lung cancer to nivolumab.